Impact of gestational diabetes mellitus on the duration of breastfeeding in primiparous women: an observational cohort study - Merja K. Laine; Hannu Kautiainen; Mika Gissler; Pirjo Pennanen; Johan G. Eriksson (BMC, 2021)
Abstract Background The impact of gestational diabetes mellitus (GDM) on the duration of breastfeeding varies between shortening and no impact. Breastfeeding seems to reduce both maternal and offspring risk for type 2 diabetes and offspring risk for overweight or obesity later in life. The aim of our study was to evaluate in primiparous women whether GDM had an influence on the duration of breastfeeding, and further, to evaluate the factors that influenced on the duration of breastfeeding. Methods The study cohort (N = 1089) consisted of all primiparous women with a Finnish background excluding women with pre-existing diabetes mellitus who lived in the city of Vantaa, Finland, gave birth to a singleton living child between 2009 and 2015, and with valid data on breastfeeding available. The diagnosis of GDM was based on a standard 75 g 2-h oral glucose tolerance test. Data were obtained from Finnish national registers and from the medical records of the city of Vantaa. Results No differences were observed in the duration of breastfeeding between women diagnosed with GDM and without GDM, 7.5 (Standard Deviation [SD] 3.7) months versus 7.9 (SD 3.5) months (p = 0.17). Women diagnosed with GDM breastfed boys for a longer duration than girls (maternal age, pre-pregnancy body mass index, marital status, educational attainment, duration of pregnancy, and smoking habits adjusted p = 0.042). Women who breastfed < 6 months were younger, were more likely smokers, had shorter education, and higher pre-pregnancy body mass index than women who breastfed over 6 months (p <  0.001 for linearity). Conclusions In primiparous women GDM did not influence breastfeeding duration. The positive health effects of breastfeeding should be emphasized especially in young, overweight and less educated women in order to minimize the risk of obesity and type 2 diabetes for themselves and their offspring.